Pengembangan Media Flipbook untuk Meningkatkan Kemampuan Pemecahan Masalah Matematis dan Minat Belajar Siswa - Raisya Hizkiya Syabina; Diar Veni Rahayu; Mega Nur Pragawati (Program Studi Pendidikan Matematika, FSTT, Universitas Pendidikan Mandalika, 2026)
This research was conducted to develop a flipbook learning media and to analyze the improvement of students' mathematical problem-solving skills and learning interest after using the media. This study employed the Research and Development method based on the Multimedia Development Life Cycle model, which consists of the stages of concept, design, material collecting, assembly, testing, and distribution. The study involved 44 ninth-grade students of SMPN 5 Tasikmalaya, consisting of an experimental class and a control class. The instruments used were essay-type test questions and a learning interest questionnaire. The validation results indicated that the developed media was feasible for use in mathematics learning. Data analysis showed that the average N-Gain score of mathematical problem-solving skills was 0.51 in the experimental class and 0.37 in the control class, both of which were categorized as moderate. The hypothesis testing result showed a Sig. (1-tailed) value of 0.029, indicating that the improvement in mathematical problem-solving skills of students in the experimental class was better than that of students in the control class. In addition, students' learning interest in the experimental class increased after the use of the flipbook media. The effect size values for mathematical problem-solving skills and learning interest were 0.596 and 0.620, respectively, both of which were categorized as moderate. Based on these findings, the developed flipbook media was deemed feasible and effective as an alternative learning medium for improving students' mathematical problem-solving skills and learning interest